EVALUATION OF HONG (2006) I-D THRESHOLD FOR LANDSLIDE EVENTS IN WEST JAVA - MUTTAQIN (NIM : 12811022), IMAM
Indonesia has considerable number of landslide events, especially in West Java. West Java Province is second province to have most landslide in Indonesia. There was 663 events of landslide in West Java Province during 1998-2014. One of the factors triggering landslide is landslide. Rainfall triggering landslide in West Java Province is used to evaluate intensity-duration threshold made by Hong et al in 2006 for global scale. Evaluation was done using 2 landslide event categories, which were landslide events accompanied by rain (545 events) and landslide events unaccompanied by rain (118 events). The result showed that there were no landslide event unaccompanied by rain which had rainfall intensity above Hong (2006) threshold. Landslide events accompanied by rain category was grouped based on each landslide susceptibility zone. After evaluate using Hong threshold, the result showed that Hong threshold is not good enough to represent landslide events in West Java Province by just passing less than 10% of events above Hong threshold. While for landslide susceptibility zone, the result showed that the higher the susceptibility, the lower rainfall intensity triggers landslide for long duration.